PENCEGAHAN SECARA DINI PENGGUNAAN ZAT NARKOTIKA BAGI KALANGAN GENERASI MUDA DI KOTA MOJOKERTO - Satriawan, Pri Agung; Soekorini, Noenik; Taufik, Moh. (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Objective Drug abuse is a serious threat that can destroy the younger generation as the future leaders of the nation. The city of Mojokerto, as a strategic area, is not immune to the circulation and abuse of drugs among teenagers. This study aims to analyze early prevention efforts against drug use among the younger generation in Mojokerto City, emphasizing the role of families, educational institutions, law enforcement agencies, and the community. The research method used is an empirical juridical approach with data collection techniques through interviews, observation, and documentation. The results of the study show that early prevention can be carried out through three main aspects, namely education, supervision, and synergistic law enforcement. The obstacles encountered include a lack of awareness among the younger generation, weak parental supervision, and limited rehabilitation facilities in the area. Thus, early prevention of drug abuse in Mojokerto City requires ongoing collaboration between families, schools, police, and local government